The Influence of Foreign Ownership on Firm Value through the Percentage of Independent Commissioners, Evidence: Manufacturing Public Companies in Indonesia - Riyan Dwi Saputro; Dwi Nastiti Danarsari (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the influence of foreign ownership on firm value, taking into account the role of the appointment of independent commissioners. Foreign ownership is identified as the independent variable, while firm value is measured as dependent variable. This study also considers the role of appointing independent commissioners as a supervisory mechanism to increase Firm value of the company. The research methodology utilizes financial data from companies listed on the capital market in the manufacturing sector, employing regression analysis through two stage least square (2SLS) and path analysis as the primary tool to test the relationships between variables. The research sample involves companies listed on the stock exchange, with annual data collected from 2016 to 2022. The findings of this research indicate that foreign ownership does not have a significant direct or indirect influence on firm value of manufacturing companies in Indonesia. Meanwhile, the percentage of independent commissioners plays a direct role in increasing firm value